Divergent mortality trends by ethnicity in Fiji. (29th October 2013) - Taylor, Richard; Carter, Karen; Naidu, Shivnay; Linhart, Christine; Azim, Syed; Rao, Chalapati; Lopez, Alan D.
Abstract Objective : To examine trends in infant mortality rate (IMR), adult mortality and life expectancy (LE) in the two major Fijian ethnic groups since 1975. Methods : Estimates of IMR, adult mortality (15–59 years) and LE by ethnicity are calculated from previously unreported Fiji Ministry of Health data and extracted from published sources. Results : Over 1975–2008: IMR decreased from 33 to 20 deaths/1, 000 live births in i‐Taukei (Fiji Melanesians); and 38 to 18 in Fijians of Indian descent. Increased adult male mortality among i‐Taukei and decline among Fijians of Indian descent led to an equal probability of dying in 2007 of 29%; while in female adults the probability trended upwards in i‐Taukei to 25%, and declined in Fijians of Indian descent to 17%. Life expectancy in both ethnicities increased until 1985 (to 64 years for males; 68 for females) then forming a plateau in males of both ethnicities, and Fijian females of Indian descent, but declining in i‐Taukei females to 66 years in 2007. Conclusions : Despite IMR declines over 1975–2008, LE for i‐Taukei and Fijians of Indian descent has not increased since 1985, and has actually decreased in i‐Taukei women, consistent with trends in adult mortality (15–59 years). Mortality analyses in Fiji that consider the entire population mask divergent trends in the major ethnic groups. This situation is most likely a consequence of non‐communicable disease mortality, requiring further assessment and a strengthened response.